IMPROVING THE EIGHTH YEAR STUDENTS’ READING COMPREHENSION BY USING NUMBERED HEADS TOGETHER (NHT) AT SMP MUHAMMADIYAH 2 KALISAT – JEMBER - Saifuddin, Muhammad; Wijaya, Dedi Malik (Educate, 2015)
Reading refers to the ability to read and understand the written text. Reading is one way to find information. The use of Numbered Heads Together (NHT) model offered the students to work in groups and help them out to improve their reading comprehension. This research was done through cycle model and the data of the research were taken from the result of observation and reading test. After having two cycles of the implementation, it showed that there was an improvement. The students‟ active participation increased from 60,86% to 73.91% while the result of students reading test increased from 60,86% of the students to 73.91% or 17 students. Based on this result, it can be concluded that the use of NHT could improve the eighth year students‟ reading comprehension.